A study on Financial Indicators of selected Pharmaceutical Companies - Rathod Vishal Mayabhai; N. D. Zala (Journal of Social Commerce, 2022)
The aim of this study is to analyses financial ratios. This study covers four different ratios; net profit margin ratio, return on assets ratio, current ratio and quick ratio as financial indicators. This study is based on secondary data and data are collected from moneycontrol.com. Researcher has selected two pharmaceuticals’ companies by using simple random sampling. Independent t-test has been used as a statistical tool and findings were discussed.